2022
DOI: 10.1155/2022/4414113
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Electroacupuncture for Depression: A Systematic Review and Meta-Analysis

Abstract: Purpose. The purpose of this systematic review and meta-analysis was to comprehensively evaluate the efficacy and safety of electroacupuncture as an effective adjunctive therapy for patients with depression. Methods. Randomized controlled trials (RCTs) about the treatment of depression by electroacupuncture therapy from inception to September 2021 were searched and collected in eight databases. HAMD, SDS, and Adverse Reactions were used as outcome indicators. The quality of relevant articles was evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Only the efficacy of EA alone was reviewed; hence, the effect of EA combined with other treatments is unknown. Further research is needed in this area ( Zhou et al, 2022 ). Fourth, studies with a high methodological quality were relatively limited, based on the Cochrane Collaboration’s assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Only the efficacy of EA alone was reviewed; hence, the effect of EA combined with other treatments is unknown. Further research is needed in this area ( Zhou et al, 2022 ). Fourth, studies with a high methodological quality were relatively limited, based on the Cochrane Collaboration’s assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Electroacupuncture shares the same advantages as acupuncture in terms of safety and effectiveness, with few adverse effects. [16,17] There have been many studies on the anti-obesity effects of electroacupuncture, [18][19][20] which is widely used for obesity treatment in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…EA therapy is a new intervention method that combines traditional needle insertion with micro-bioelectric current to provide continuous positive stimulation. Numerous studies have been conducted on the mechanism of the effect of EA intervention on depression, and the efficacy of EA in treating depression has gradually been verified [4,5]. The study by She et al [6] showed that a certain improvement effect on the depressed rat model was achieved using EA intervention (Baihui point and Yintang point), which was closely associated with the plasticity of hippocampal synapses.…”
Section: Introductionmentioning
confidence: 99%